6-sialyllactose ameliorates dihydrotestosterone-induced benign prostatic hyperplasia through suppressing VEGF-mediated angiogenesis - Kim, Eun-Yeong; Jin, Bo-Ram; Chung, Tae-Wook; Bae, Sung-Jin; Park, Hyerin; Ryu, Dongryeol; Jin, Ling; An, Hyo-Jin; Ha, Ki-Tae (BMB reports, 2019)
Benign prostatic hyperplasia (BPH), a common disease in elderly males, is accompanied by non-malignant growth of prostate tissues, subsequently causing hypoxia and angiogenesis. Although VEGF-related angiogenesis is one of the therapeutic targets of prostate cancer, there is no previous study targeting angiogenesis for treatment of BPH. Dihydrotestosterone (DHT)- induced expressions of vascular endothelial growth factor (VEGF) in prostate epithelial RWPE-1 cells and human umbilical vascular endothelial cells (HUVECs). Conditioned media (CM) from DHT-treated RWPE-1 cells were transferred to HUVECs. Then, 6SL inhibited proliferation, VEGFR-2 activation, and tube formation of HUVECs transferred with CM from DHT-treated RWPE-1 cells. In the rat BPH model, 6SL reduced prostate weight, size, and thickness of the prostate tissue. Formation of vessels in prostatic tissues were also reduced with 6SL treatment. We found that 6SL has an ameliorative effect on in vitro and in vivo the BPH model via inhibition of VEGFR-2 activation and subsequent angiogenesis. These results suggest that 6SL might be a candidate for development of novel BPH drugs. [BMB Reports 2019; 52(9): 560-565]